Shamba shape up series 13 - Ep 11: Financial Literacy, chicken, climate literacy and soil health - Burra, Dharani Dhar; Ramírez Villegas, Julián Armando; Rottmann, Sophie; Galgallo, Diba; Murage, Paul; Campbell, David (2023)
"Shamba Shape Up" is a popular television show in East Africa that focuses on agricultural education and improvement. The show features a team of experts who visit different farms, providing practical demonstrations and advice to farmers on various aspects of agriculture, such as livestock rearing, crop cultivation, farm management techniques, and sustainable practices. It aims to educate and empower farmers with valuable information and skills to enhance productivity, increase yields, and improve their livelihoods. The program combines entertainment with education, using a reality TV format to engage viewers and encourage the adoption of better farming methods. This episode, part of Series 13, was broadcast during the 2023 long rains in Kenya. It focuses on: (i) Setting up a successful chicken business; (ii) managing farm finances; (iii) reading and planning based on weather forecasts; and (iv) maintaining soil health in dry areas. The financial literacy content is funded by the Livestock & Climate (L&C) initiative.